The role of control system in increasing corporate social performance: The use of levers of control - Fauzi, Hasan; Abdul Rahman, Azhar (Indonesian Center for Social and Environmental Research and Development, 2008)
One important instrument to be used in the control system design is strategic behaviors that can lead to the expected organization performance.Referring to the extended definition of strategic behavior using stakeholder-based strategic behavior, corporate social performance is kind of strategic behavior to be influenced by using control system. This paper discusses how control system, using Simons’ levers of control can play important role in increasing the corporate social performance. The interaction between control system, including belief system, boundary system, diagnostic control system, and interactive control system, as well as the corporate financial performance (CFP) can affect the corporate social performance (CSP) due to fact that increase in CFP resulting from the appropriate use of control system components enables the company has more chance to do the CSP. The levers of control are deemed to form an integral part of employee socialization and support the development of an organization’s culture, the system of shared beliefs, values, norms, and mores of organizational members which are deemed to be a primary determinant of the direction of employee behavior.